ANALISIS KEBIJAKAN HUTANG DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Pandiangan, Kiki Dewi Sinta; Efriyenti, Dian (SCIENTIA JOURNAL, 2022)
ABSTRACT Fluctuations in the debt-to-equity ratio of manufacturing companies for the 2016-2020 period indicate that the company's own funds are not consistently used. Fluctuations in net profit margin result in fluctuations in price to book value. This fluctuating PBV has an impact on the company's image. The purpose of this study is to find out the effect of DER and NPM on PBV by using secondary data on annual financial reporting. The sample used purposive sampling method. a population of 51 manufacturing companies in the consumer goods sector from 2016-2020 obtained a sample of 8 companies. Analysis of research data using classical assumption test, multiple linear regression, t test, f test, coefficient of determination. DER has a significant effect on PBV with a significance value of 0.00 < 0.05, t count 5.849 > 2.026. NPM has a significant effect on PBV with a significance value of 0.00 <0.05, t count 5,790 > t table 2,026, if tested together DER and NPM have a significant effect on PBV with a number 0.000 < 0.05, F count 35,223 > Ftable 3. 24.